Studi Literatur: Analisis Berbagai Pendekatan Penyelesaian Konflik Agraria di Provinsi Bangka Belitung - Apriyansyah, Apriyansyah; Nabyla, Dessyana; Rangkuti, Masitoh; Sakiri, Sahli (Indonesian Democracy Research Center, 2022)
Agrarian conflict is a problem that often occurs in Indonesia, including in the Bangka Belitung archipelago province. Settlement of agrarian conflicts requires appropriate and varied approaches to address the various factors that cause these conflicts. Therefore, this study uses qualitative methods in which qualitative research methods help explain phenomena in depth and are carried out by gathering as deep information as possible. Therefore, qualitative methods emphasize observing phenomena and studying the meaning of these phenomena. The results of the analysis show that there are various approaches that can be used in resolving agrarian conflicts, such as legal approaches, participatory approaches, economic approaches, and political approaches. In addition, this study also discusses the factors that cause agrarian conflicts in the Bangka Belitung archipelago province, such as different views between local communities and companies, limited local community access to resources, and a lack of policies that support agrarian conflict resolution. This study is expected to provide a deeper understanding of agrarian conflicts in the Bangka Belitung Archipelago Province and become the basis for developing more effective conflict resolution approaches in the future. In this paper, we use the Conflict Theory put forward by Karl Marx, who asserts that this theory is triggered in the relationship of conflict between the bourgeois class against the proletariat class in seizing economic rights (means of production).